Determinants of online group buying behaviour: the moderating role of informational social influence - Tracie Chin, Sook Harn; Geoffrey Harvey Tanakinjal; Stephen Liason Sondoh Jr.; Hamid Rizal (Penerbit Universiti Kebangsaan Malaysia, 2014)
This study aims to develop a theoretical model to explicate online group buying behaviour. The research was based on Technology Acceptance Model (TAM) and two determinants of perceived enjoyment and informational social influences. A total of 150 usable questionnaires are collected and analysed using a multiple regression analysis to examine the strength of relationships between these variables. The results suggest perceived ease of use has no significant influence on online group purchase intention; however, perceived usefulness and perceived enjoyment completely mediate the relationship between perceived ease of use and purchase intention. Interestingly, the study indicates informational social influence has no moderating effect on determinants of purchase intention towards online group buying. The results of this study offer marketers with better insights that would help them develop effective strategies to attract online group buying users and increase sales profit.